Study of Chemical Analysis of Formaldehyde in the Melamine Tableware Visible Spectrophotometry - Tangdiongga, Rita R.; Mandey, Lucia C.; Lumoindong, Frans (Jurnal Ilmu dan Teknologi Pangan, 2015)
Formaldehyde in melamine can appear at events depolymerization, formaldehyde particles appear as monomers and produce toxins that are harmful to health. In the manufacture of melamine tableware, manufacturers often add formadehyde unbalanced with phenol as a raw material. This study aims to determine the content of formaldehyde in melamine tableware. Looks Rays Spectrophotometric Method, guided by the regulatory Food and Drug Monitoring Agency (BPOM) No. HK.03.1.23.07.11.6664 in 2011. The results showed that the oval plate ware tableware containing 4.68% formaldehyde levels. High levels of formaldehyde in melamine tableware melamine production system resulting in uncontrolled. While four other samples of melamine tableware undetectable formaldehyde content. Keywords : formaldehyde, melamine, tableware